Bhagvad Gita, gut microbiota, and mental health - Hitesh Chandrakant Sheth (Wolters Kluwer Medknow Publications, 2021)
There is a mysterious relationship between the diet and human behavior, which is reflected in the writings of many ancient scientists and philosophers and the same thing is also echoed in day-to-day conversations of many cultures, interspersed with nuggets of ancient wisdom. However, it is hard to find a standard classification in the modern science that links different diets to various human behavioral patterns. The recent research shows that, although gut microbiota residing in a human body influences its physical health and mental health, their diversity can be influenced by human dietary patterns. Thus, along with the medicine, diet too has emerged as a key player in the regulation of our physical and mental health. Therefore, dietary modification along with necessary medicines may be recommended for the management of various physical and mental disorders.